Analysis of Elephant-Human Conflict and Community Perceptions Around Conservation Areas on The Island of Sumatra: A Literature Review - Magdalena, Ellen Sukma Mega; Suciani, Tanti; Wakhidah, Anisatu Z. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The world's elephant population is experiencing a significant decline and is a serious concern in conservation efforts. Conflicts between elephants and humans are becoming an increasingly widespread problem, especially on the island of Sumatra. This study aims to assess people's perceptions of elephant conflicts, the impacts and the education needed to increase public awareness of the importance of elephants. Through the literature study method, it is known that people's perception of elephant conflict tends to be negative, most people have the perception that elephants are crop pests and must be destroyed. The impact of conflicts between elephants and humans such as damage to agricultural land, death of elephants and humans, and damage to infrastructure. To realize a solution to this conflict, it is necessary to conduct comprehensive educational counseling to the community, such as the implementation of a moratorium on concession licensing, forest enrichment, the formation of effective patrol teams, technological support in monitoring forest changes, and socialization to surrounding communities about elephants. Collaboration between the government, communities, and non-governmental organizations will be beneficial in addressing human-elephant conflicts. With these efforts, it is hoped that disputes between elephants and humans can be minimized and the increasingly threatened elephant population will be maintained and sustainable.